Św. Augustyn a paradoks zła - Nowakowski, Dawid (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
This article is an attempt of representing St. Augustine’s struggle against the greatest problems of Christian ethics, namely, the problem of evil. After the introduction of the philosophical grounds of the problem, we will turn to the outline of the way the Bishop of Hippo has gone through in the quest of the rational explanations for the existence of evil. An analysis of Augustine’s works has shown that he lost his hope to find any sensible answer to this question with the lapse of time, and abandoned himself to an almost blind faith. The Saint leaves us all by ourselves with this anxious question about evil.